Incidence of Symptomatic Femoroacetabular Impingement: A 4-Year Study at a National Collegiate Athletic Association Division I Institution. Issue 4 (12th April 2022) - Safran, Marc R.; Foard, Sara James; Robell, Kevin; Pullen, W. Michael
Background: Femoroacetabular impingement (FAI) is an increasingly recognized cause of hip pain in young athletes. Although there are multiple studies that describe the radiographic prevalence of FAI in athletes, its true incidence within this population is unknown. Purpose: To report on the overall and sport-specific incidence of symptomatic FAI in National Collegiate Athletic Association (NCAA) Division I athletes. Return-to-sport times were reported for patients treated operatively. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective review was conducted to identify all reported hip injuries within a large, multisport NCAA Division I institution. Hip injuries were stratified into FAI, general pain/dysfunction, musculotendinous, ligament, bursitis, bone stress, contusion, and other. FAI was diagnosed based on history, physical examinations, imaging, and symptomatic relief after a diagnostic injection. Descriptive statistics were used to calculate the overall and sport-specific incidence, and chi-square analysis was performed to identify contingency data. Results: In a 3-year period, a total of 5319 musculoskeletal injuries occurred in 1072 athletes. There were 491 (9.2%) hip injuries that occurred in 288 athletes, of which 40 injuries were FAI. The overall incidence of symptomatic FAI was 3.0% of the total population, 3.7% of all injured athletes, and 13.9% of athletic hip injuries. There were no statistically significant differences in FAI rates among male and female athletes overall or among male and female athletes within similar sports. Of the 19 athletes who were treated nonoperatively, 2 failed to return to play: 1 secondary to multiple musculoskeletal injuries and 1 related to cardiac issues. There were 21 hips in 20 patients that were treated operatively, with 1 athlete failing to return to sport. Return to play occurred at a mean of 202 days (range, 81-360 days) after hip arthroscopic surgery. Conclusion: In this large, multisport NCAA Division I cohort, the overall incidence of symptomatic FAI was 3.0% and represented 13.9% of hip injuries. The successful management of FAI with return to play was achieved by both nonoperative and operative treatment methods. The relatively low incidence of symptomatic FAI, despite reports of a high prevalence of FAI morphology in athletes, serves to emphasize the importance of clinical evaluations in treating patients with FAI.